Modularizing services: A modified HoQ approach - Geum, Youngjung; Kwak, Ran; Park, Yongtae (Computers & industrial engineering, 2012)
► This paper proposes a framework for service modularization using HoQ. ► The relationship matrix modularizes services based on the strategic focus. ► The roof matrix modularizes services based on the component relationship. Compared with manufacturing, the modularization of services has rarely been dealt with, despite its potential benefits. More specifically, the question of how to modularize services in the practical context is still an unexplored subject. In response, this paper proposes a solid framework for service modularization, by employing and modifying the House of Quality (HoQ) structure in Quality Function Deployment (QFD) using two ways: driver-based approach and interrelationship-based approach. Firstly, module drivers representing the service characteristics are identified through a comprehensive literature review. In this step, twofold module drivers are identified: one for common and the other for service-specific. Secondly, by considering the interdependent nature of service offering, service is decomposed according to the three predefined dimensions: service process, service outcome, and prerequisites for the service. Service modularization is then conducted using HoQ structure; the relationships between module drivers and decomposed service components are analyzed in the Strategic Modularability Matrix (SMM), whereas the interrelationships among service components are identified in Interrelated Components Modularability Matrix (ICMM). Finally, a clustering analysis is conducted to identify the module candidates. In order to illustrate the utility of the proposed approach, a restaurant service is exemplified. This study contributes to the field by filling the void left by the service sector by applying the service-specific module drivers to modularize services, as well as analyzing the relationship among service components using three interrelated dimensions.